Spatial patterns and influencing factors of soil SOC、DOC、ROC at initial stage of vegetation restoration in a karst area - Wu, Yunjie; Wang, Runze; Zhang, Mingyi; He, Peiran; Wu, Yujie; Tian, Xin; Zhang, Jianli (Frontiers in Environmental Science, 2023)
In this study, we compared the complete succession transects under distinct geomorphological environments regarding non-karst, karst, and karst vegetation restoration landforms in a National Nature Reserve, Caohai (Guizhou Province, China). To explore the driving mechanism of vegetation restoration on the change of soil physical and chemical properties and the synergistic effect of soil carbon cycle and vegetation restoration succession process in karst area, the content distribution characteristics of soil organic carbon (SOC), readily oxidizable carbon (ROC), and dissolved organic carbon (DOC) were analyzed, and the geomorphology, spatial location, and interaction effects were investigated by using a generalized linear mixed model (GLMM) as well. The results showed that topsoil organic carbon content was lower in the vegetation restoration area than those in unrepaired area and non-karst area. Soil ROC content followed a significant descending order of karst area > vegetation restoration area > non-karst area. However, there were no significant differences in soil DOC across distinct areas. Vegetation coverage was markedly improved as a result of dominant plants changed (from Gramineae to Gramineae + Compositae) in the karst vegetation restoration area. SOC decreased in relation to increased depth in the karst area, yet this positive correlation was weakened under vegetation restoration on the upper-slope and even reversed after the lower-slope was rehabilitated. The GLMM analysis suggested that geomorphology constrained topsoil SOC, and geomorphology and spatial greatly affected topsoil ROC. In comparison, karst revegetated area exhibited large effects on soil ROC in the Caohai. This study hopes to supplement understandings of ecological functions and vegetation restoration in karst areas, as well as responses to regional carbon cycling.